Using the Multiple Correspondence Analyses to Study the Addiction of Drug and Alcohol in Iraq - Rasheed, Aseel Abdul Razzak; Rasheed, Husam A.; Sadik, Nazik J. (International Journal of Psychosocial Rehabilitation, 2020)
Drug and alcohol addiction are a social problem that emerged last decades in Iraq. In this study, we discuss the problem of an addiction by using multiple correspondence analyses (MCA). MCA is one of the multivariate methods as it is used to study the correlation strength that exists between more than two categorical variables. The data classifies according to Iraqi governates, gender, and patient status (inpatient or outpatient). A relation between variables was clarified through Burt matrix. Our results show the drug addiction is the larger than alcoholic addiction in all Iraqi governates. The main reason of drug addiction is taking its continuously without consulting a specialist.